Menanamkan kesadaran hidup rajin pada siswa taman kanak-kanak dengan metode fun learning - Syah, Angelique Regina; Chriswanto, Evelyn Jennis; Soetikno, Elbert; Anastasia, Njo (Nur Science Institute, 2024)
Living diligently is one of the essential aspects of every individual's life. Awareness to cultivate diligence can be acquired from various sources, especially the immediate environment. This trait should be instilled from childhood because forming one's character is optimal during one's golden age. This community service aims to cultivate awareness and encourage motivation among kindergarten students regarding the importance of having diligence within themselves. This is because diligence is the initial step towards achieving the goals of every individual. The method used in this community activity is done in three steps: preparation, implementation, and evaluation. Learning activities are also conducted through fun learning methods to attract students' interest and prevent boredom. The results of this community service activity show a positive response from kindergarten students, namely a change towards a better direction before and after the activity. Kindergarten students become more aware and motivated to be diligent in everything.